Studi Analisis : Praktek Penetapan Materialistis dalam Audit atas Akun Aset Tetap oleh KAP ABC pada PT. X - Safero, Izzat Akhmad; Nanda Wahyu Indah Kirana (Lembaga Pengembangan Kinerja Dosen, 2025)
Determining the materiality level is an important step in planning and implementing a financial statement audit, especially in accounts with significant value such as fixed assets. However, in practice, auditors often face challenges in determining the right materiality level for complex accounts such as fixed assets, especially in companies that have not gone public and are in the development stage. This study aims to analyze the practice of determining the materiality level in the audit procedure for fixed asset accounts at PT. X for the 2024 financial year. The research method used is qualitative with a case study approach through document observation and interviews at the XYZ Public Accounting Firm. The results of the study show that auditors set materiality based on total assets because PT. X has not gone public and is in the development stage. The auditor found a correction in the calculation of accumulated depreciation of fixed assets of Rp24,128,825, but this value was still below the overall materiality limit of Rp186,704,652. Therefore, the fixed asset account is concluded to have been presented fairly and free from material misstatement. This study supports the importance of determining materiality based on professional judgment to improve audit quality.